VIOLENCIA CONTRA LA MUJER. UNA APROXIMACIÓN A SU DISMINUCIÓN DESDE LA ESCUELA SECUNDARIA - Arias Méndez, Marilé; García Pérez, Jacqueline (Gênero & Direito, 2020)
“Women and girls face various types of violence (physical, economic and psychological), ranging from sexual comments and whistling, fondling, and raping, to the most extreme form: femicides,” as stated by the United Nations (UN) in a written communication. This worldwide organization called on governments, the private sector and society in general to eradicate the violence suffered by two out of three women; This particular problem in Mexico also shows alarming statistics which, in order to be visible nationwide, the States have issued violence alerts as a preventive measure.Education plays an important role in the transformation of this situation, rapists and rape victims are the result of educational processes that take place in classrooms, in the family and social contexts that have been organized about them, which obviously have not been completely efficient. In this regard, the intention is to organize clubs and work in favor of no gender-based violence since high school where standards and values ​​are established, promoting women respect and consideration, and the demands of this level of education are maintained